Can separation of the scrotal sac in proximal hypospadias reliably predict the need for urethral plate transection?. Issue 2 (April 2016) - Arnaud, Alexis; Ferdynus, Cyril; Harper, Luke
Summary: Introduction: One of the main challenges in proximal hypospadias repair is correcting curvature. The best technique to achieve this remains the object of debate. Indeed, some authors believe the urethral plate should be kept and used as often as possible. In some cases, however, even after extensive mobilization and dorsal plication, significant curvature remains and it is necessary to transect the urethral plate. Having a reliable pre-dissection marker of the need for urethral transection would be useful in choosing a technique.We wanted to determine if presence of marked separation of the scrotal sac (SSS), also referred to as bifid scrotum, could reliably predict the need for urethral plate transection. Study design: We prospectively enrolled a series of boys with proximal hypospadias. We noted age, degree of hypospadias, meatal position, presence of cryptorchidism, and presence or absence of SSS. During surgery we fully degloved the penile shaft, freeing all ventral tissues, and radically dissected the more proximal bulbar urethra. We then performed an erection test. If there was residual curvature <30° we performed a dorsal plication, if it was >30° we transected the urethral plate. Results: Twenty-nine patients were included, of whom 18 presented SSS. The average age was comparable in both groups, as was type of hypospadias and meatal position. We estimated transection of the urethral plate to be necessary in 15 out of the 18 children with SSS, and 2 out of the 11 children without SSS. The relative risk for requiring urethral plate transection in case of SSS in this series was 4.58. Conclusion: Techniques that commit to urethral plate transection are criticized because they preclude using the urethral plate. In our study presence of SSS was predictive for the need to transect the plate. Obviously one can decide to keep the urethral plate at all cost, and mobilize it more than we did, or accept more residual curvature, but in reality our aim was to determine a preoperative marker allowing us to define a patient category. We believe presence of SSS is a marker of severity, and that this "severity" translates into "a less usable urethra". As recent studies caution us about the evolution of the reconstructed native urethra and the possibility that it may not grow as well as the other penile tissues, we believe this extra information could influence the surgeon's decision as to the most appropriate technique for each patient. Table Results of bivariate analysis. Results Total No SSS SSS p Age, years 4.2 3.4 4.7 0.68 Urethral transection 17 (58.6%) 2 (18.2%) 15 (83.3%) 0.001 A p-value <0.05 was considered statistically significant.